Watch me grow integrated (WMG-I): protocol for a cluster randomised controlled trial of a web-based surveillance approach for developmental screening in primary care settings. Issue 8 (17th August 2022) - Eapen, Valsamma; Liaw, Siaw-Teng; Lingam, Raghu; Woolfenden, Susan; Jalaludin, Bin; Page, Andrew; Kohlhoff, Jane; Scott, James G; Lawson, K D; Lam-Cassettari, Christa; Heussler, Helen; Descallar, Joseph; et al.
Abstract : Introduction: The increasing prevalence of developmental disorders in early childhood poses a significant global health burden. Early detection of developmental problems is vital to ensure timely access to early intervention, and universal developmental surveillance is recommended best practice for identifying issues. Despite this, there is currently considerable variation in developmental surveillance and screening between Australian states and territories and low rates of developmental screening uptake by parents. This study aims to evaluate an innovative web-based developmental surveillance programme and a sustainable approach to referral and care pathways, linking primary care general practice (GP) services that fall under federal policy responsibility and state government-funded child health services. Methods and analysis: The proposed study describes a longitudinal cluster randomised controlled trial (c-RCT) comparing a 'Watch Me Grow Integrated' (WMG-I) approach for developmental screening, to Surveillance as Usual (SaU) in GPs. Forty practices will be recruited across New South Wales and Queensland, and randomly allocated into either the (1) WMG-I or (2) SaU group. A cohort of 2000 children will be recruited during their 18-month vaccination visit or opportunistic visit to GP. At the end of the c-RCT, a qualitative study using focus groups/interviews will evaluate parent and practitioner views of the WMG-I programme and inform national and state policy recommendations. Ethics and dissemination: The South Western Sydney Local Health District (2020/ETH01625), UNSW Sydney (2020/ETH01625) and University of Queensland (2021/HE000667) Human Research Ethics Committees independently reviewed and approved this study. Findings will be reported to the funding bodies, study institutes and partners; families and peer-reviewed conferences/publications. Trial registration number: ANZCTR12621000680864.